Антикоррозионная защита ответственных деталей аварийно-спасательного оборудования гальванопокрытиями Ni-Sn 1. Особенности осаждения и завистимость состава покрытий от условий синтеза - Reva Ольга; Kuznetsov Борис; Uglov В.; Urbanovich Е. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The research of the laws the Ni-Sn alloy formation from new complex type electrolytes is carried out. Novel combined pyrophosphate-glycine-chloride solutions that do not require heating, in which blocked the phenomenon of cathodic passivation are developed. The chemical composition of the films in depends on the synthesis conditions and electrolyte compositions are investigated. The ways of regulation the components maintenance in an alloy are developed.